Towards creating a nation of engineerpreneur. - Jusoh, Rosnani; Hussain, Afifuddin Husairi; Abdul Rahman, Fadzilah; Che Ani, Adi Irfan; Hussin, Haziyah (World Academy of Science, Engineering and Technology, 2013)
New conceptualizations were introduced to address the emerging need to develop innovativeness and creativity attitudes in future engineering professional . Thus, entrepreneurial engineering education needs an environment where future engineers can be formed through practical learning and the interaction with forces, ideas and inspirations, in the final perspective of effectively identifying, acquiring, developing, and transferring technology into new business products and services. This paper aims to investigate the characteristics of a successful entrepreneur for engineering students. A questionnaire was used to measure the level of entrepreneurial competencies. The questionnaire was based on the Personal Entrepreneurial Competence Model, developed by McClelland Individual. Participants were recruited from the final year students of eight programs under the Faculty of Engineering. Of the 432 questionnaires distributed, 210 were collected back, giving a response rate of approximately 49%. Findings suggest that final year engineering students have respectable entrepreneurial attitudes and behaviors, and are competent to be engineerpreneur. The study also recommended that we need an environment that does not insist that engineers become entrepreneurs, but one where the two can meet, and business leaders can organize our nation effectively.